THE ROLE OF BAWASLU IN MONITORING CHILDREN'S INVOLVEMENT DURING THE 2019 SAMARINDA CITY ELECTION CAMPAIGN - Dini Astarina; Lilik Andaryuni; Suwardi Sagama (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Due to the researcher's interest and concern for child protection in the political realm, especially the involvement of children in election campaigns, the researcher wants to know how legal protection is for children during the campaign period during the simultaneous elections held in 2019, because the researcher considers this matter very urgent to be discussed by the public There is also a lack of socialization from election management institutions including Bawaslu as a supervisory institution regarding children who should be protected before the democratic party which is held every 5 years per term of office. The research method used in this research is an empirical normative research method because it uses in-depth study, requires a legal or normative approach as well as experience or observations in the field, looking at the role of related institutions and their impact on society, especially on children. Apart from that, in this research the author uses descriptive qualitative data analysis with a discourse analysis approach, this analysis technique is used by the author to analyze people's interactions, discourse analysis focuses more on the social context where communication occurs between respondents and researchers, then describes the data obtained in the form of explanations and sentence descriptions. The results obtained from this research can be concluded that Bawaslu or the Samarinda City Election Supervisory Agency as a supervisory institution and as one of the election organizers has an important role in supervising children's involvement because Bawaslu is the one who is in direct contact with the various stages of the election monitoring process, including the ongoing campaign. There are various obstacles faced by Bawaslu so that in exercising its authority it is not optimal, the steps that Bawaslu must take in supervising children's involvement are to strengthen synergy with the community and the Gakkumdu Center or Integrated Law Enforcement Center and implement child-friendly campaigns. The involvement of children in the campaign, especially in the 2019 Simultaneous Elections, is an act that violates the law as regulated in Law of the Republic of Indonesia No. 23 of 2002 which was amended to become Law of the Republic of Indonesia No. 35 of 2014 concerning Child Protection, which was then also regulated in the Republic of Indonesia Law. Indonesia No. 7 of 2017 concerning General Elections, further supervision of campaigns is regulated in Bawaslu Regulation No. 28 of 2018 concerning Supervision of General Election Campaign Stages, because this research was conducted in Samarinda City, Samarinda City Regional Regulation No. 10 of 2013 is also included in it.